Titanium oxide vertical resistive random‐access memory device. (1st July 2015) - Fryauf, David M.; Norris, Kate J.; Zhang, Junce; Wang, Shih‐Yuan; Kobayashi, Nobuhiko P.
Abstract : Pt/TiO2 /Pt vertical resistive random‐access memory switching devices were fabricated in a vertical three‐dimensional structure by combining conventional photolithography, electron‐beam evaporation for electrodes and atomic layer deposition for dielectric layers. The active switching cross‐sectional area was ∼0.02 µm 2, which is comparable to nanosized devices that require more elaborative fabrication processes. Structural integrity and electrical characteristics of the vertical memory device were analysed by cross‐sectional scanning, transmission electron microscopy and current–voltage characteristics.